Use the standard equation of the circle given by:

\(\displaystyle{\left({x}-{h}\right)}^{{{2}}}+{\left({y}-{k}\right)}^{{{2}}}={r}^{{{2}}}\)

where (h,k) is the center and r is the radius.

Substitute h=7, k=2, and r=5:

\(\displaystyle{\left({x}-{7}\right)}^{{{2}}}+{\left({y}-{2}\right)}^{{{2}}}={5}^{{{2}}}\)

\(\displaystyle{\left({x}-{7}\right)}^{{{2}}}+{\left({y}-{2}\right)}^{{{2}}}={25}\)

Result:

\(\displaystyle{\left({x}-{7}\right)}^{{{2}}}+{\left({y}-{2}\right)}^{{{2}}}={25}\)

\(\displaystyle{\left({x}-{h}\right)}^{{{2}}}+{\left({y}-{k}\right)}^{{{2}}}={r}^{{{2}}}\)

where (h,k) is the center and r is the radius.

Substitute h=7, k=2, and r=5:

\(\displaystyle{\left({x}-{7}\right)}^{{{2}}}+{\left({y}-{2}\right)}^{{{2}}}={5}^{{{2}}}\)

\(\displaystyle{\left({x}-{7}\right)}^{{{2}}}+{\left({y}-{2}\right)}^{{{2}}}={25}\)

Result:

\(\displaystyle{\left({x}-{7}\right)}^{{{2}}}+{\left({y}-{2}\right)}^{{{2}}}={25}\)